Analysis of the Local Precipitation Trends in the Podkarpackie and Lubuskie Voivodeships - Kubiszyn, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The type of precipitation is one of the factors taken into consideration when deciding on the most optimal drainage system. Drainage systems are used to prevent the landslides caused by water erosion. Rainfall affect the rate of infiltration and the intensity of surface runoff and thus the occurrence, course and effectiveness of erosion processes [1, 2, 3].
Keywords: local precipitation trends; Mann-Kendall test; decision-making process map; risk management